Faktor Risiko Kejadian Malaria Di Desa Lubuk Nipis Kecamatan Tanjung Agung Kabupaten Muara Enim - Ahmadi, Supri; Sulistyani, Sulistyani; Raharjo, Mursid (Master Program of Environmental Health, Faculty of Public Health, Diponegoro University, 2009)
ABSTRACT Background: Malaria was still a serious health problem in Indonesia. It was widely spread in many areas with various level of infection. In 2007, Annual Malaria Incidence (AMI) in Muara Enim district, was 24.77 0/00. It was higher than National Annual Malaria Incidence (AMI 10 0/00). The research aimed to find out risk factors that influence malaria incidence in Muara Enim . Method: This study was designed as case control or retrospective study. As the case of the study, there were fifty four (54) malaria positive people were involved. Rapid survey was employed to select 54 respondents from negative of malaria. Thus, they were totally 108 respondents. Result: It was found three species of anopheles mosquitoes as suspected vectors, which are An. nigerimus, An. latifer and An. maculatus. Those species were found at the puddles, rice field, pool, river, and public toilets. Factors that contributed to malaria incidence were the water bodies or ponds around the house, not using bad net and coil to avoid mosquitoes. Conclusion: Most of the respondent had not used bed net while sleeping as risk factors to the incidence malaria in Muara Enim District. Key words : Malaria, environmental factor, behavioral factor, Muara Enim